Southwest view of an ancient edifice called Ashmole's House in Ship Yard, Temple Bar, Fleet Street - Schnebbelie, Robert Blemmell (Tufts Archival Research Center, 2008)
Supposed to have been the residence of Elias Ashmole, Esq., the celebrated antiquary. This illustration is from Robert Wilkinson's "Londina Illustrata," vol. 1.